SF-YOLO: A Physics-Guided Framework for Ship Detection in Foggy Maritime Scenarios - Zhou Yang; Tujie Wu; Ruoling Deng; Hubo Chu; Haitao Liu (Journal of Marine Science and Engineering, 2026)
Foggy ship detection frequently suffers from image degradation, blurred object contours and a high missed detection rate. Moreover, most existing maritime datasets lack adequate real fog samples. To solve the above problems, in this paper, the Fog-SMD is constructed on the basis of atmospheric scattering principles and fractal theory in combination with a diffusion model to enrich samples covering various fog scenarios. On this basis, we develop an improved SF-YOLO model that takes YOLOv12 as the basic framework. By embedding the shallow–deep adaptive feature fusion module, scattering-guided refinement module and spatial-frequency dual feature attention module, the model can effectively alleviate feature loss resulting from image degradation in foggy environments. Weighted-EIoU loss is introduced to optimize the bounding box regression and reduce the localization deviation of slender ship targets. The experimental results show that SF-YOLO achieves mAP@50 and mAP@50:95 values of 79.3% and 61.6%, respectively, and outperforms mainstream detection algorithms; compared with YOLOv12n, it improves mAP@50:95 from 59.6% to 61.6%, with only a slight increase in parameters from 2.5 M to 2.8 M, providing a new solution for the practical deployment of detection systems and all-weather maritime monitoring in low-visibility foggy scenarios.

An integrated FDEMATEL-ISM and Bayesian network approach for dynamic deduction of electrical safety risks in battery electric ships - Ruoling Zhou; Liu Yang; Ailong Fan; Chengpeng Wan; Lei Wang (Ocean Engineering, 2026)

Organic fertilizer substitution for chemical fertilizer has a stronger effect on soil bacterial specialists than on generalists - Ruoling Zhang; Weidong Xu; Hao Liu; Xiang Long; Jiaqing Zhou; Min Xu; Hui Cao; Feng Wang (Plant and Soil, 2025)

Fire risk assessment of electric ships on inland waterway based on GT-FFTA: A case study of China - Liu Yang; Junzhang Yang; Ailong Fan; Ruoling Zhou; Lei Wang (Ocean Engineering, 2025)

Moderate deep banding of phosphorus enhanced winter wheat yield and fertilizer uptake efficiency by promoting nutrient absorption and translocation of pre-anthesis nutrient - Yang Zhou; Zhenyan Li; Yongqiang Li; Jinwei Li; Ruoling Ma; Xiang Lin; Shubo Gu; Jing Yang; Dong Wang (Field Crops Research, 2025)

Impact of PM2.5 exposure in old age and its interactive effect with smoking on incidence of diabetes - Anthony Chen; Jiaqian Yin; Ying Ma; Jian Hou; Weiju Zhou; Zhongliang Bai; Xia Qin; Zhi Hu; Yuntao Chen; Eric J. Brunner; Haidong Kan; Ruoling Chen (Science of The Total Environment, 2024)

Oxidation with potassium ferrate for the one-pot preparation of carboxylated cellulose II nanocrystals - Yunxiao Liu; Xiaolin Li; Yulong Li; Hongze Xu; Ruoling Liu; Yi Zhang; Zhenchao Zhang; Yuan Yuan; Lu Zong; Lijuan Zhou; Jianming Zhang (Carbohydrate Polymers, 2024)